Tocopherol attenuates the oxidative stress of BMSCs by inhibiting ferroptosis through the PI3k/AKT/mTOR pathway - Lan, Dongmei; Yao, Chao; Li, Xue; Liu, Haijiang; Wang, Dan; Wang, Yan; Qi, Shengcai (Frontiers in Bioengineering and Biotechnology, 2022)
Oxidative stress can induce bone tissue damage and the occurrence of multiple diseases. As a type of traditional medicine, Tocopherol has been reported to have a strong antioxidant effect and contribute to osteogenic differentiation. The purpose of this study was to investigate the protective effect of Tocopherol on the oxidative stress of rat Bone Marrow-derived mesenchymal Stem Cells (BMSCs) and the underlying mechanisms. By establishing oxidative stress model in vitro, Cell Counting Kit-8 (CCK-8), Reactive Oxygen Species (ROS) analysis, Western blot (WB), Real-Time PCR (RT-PCR), Alkaline Phosphatase (ALP) Staining and Alizarin Red Staining (ARS) valuated the effects of Tocopherol on the cell viability, intracellular ROS levels and osteogenic differentiation in BMSCs. In addition, ferroptosis related markers were examined via Western blot, RT-PCR and Mito-FerroGreen. Eventually, PI3K/AKT/mTOR signaling pathway was explored. We found that Tocopherol significantly maintained the cell viability, reduced intracellular ROS level, upregulated the levels of antioxidtive genes, promoted the levels of osteogenic related protein and mRNA of BMSCs stimulated by H2O2. More importantly, Tocopherol inhibited ferroptosis and upregulated the phosphorylation levels of PI3K, AKT and mTOR of BMSCs upon H2O2 stimulation. In summary, Tocopherol protected BMSCs from oxidative stress damage via inhibition of ferroptosis through the PI3K/AKT/mTOR pathway.